Triatoma vitticeps (Stal, 1859) (Hemiptera, Triatominae): A Chagas Disease Vector or a Complex of Vectors? - Chaboli Alevi, Kaio Cesar [UNESP]; Caris Garcia, Ariane Cristina [UNESP]; Guerra, Ana Leticia [UNESP]; Figueiredo Moreira, Felipe Ferraz; Oliveira, Jader de [UNESP]; Rosa, Joao Aristeu da [UNESP]; Vilela de Azeredo Oliveira, Maria Tercilia [UNESP] (Amer Soc Trop Med & Hygiene, 2018)
Triatoma vitticeps is a Chagas disease vector that was found infected with Trypanosoma cruzi in homes. As this species is endemic from Brazil (Bahia, Espirito Santo, Minas Gerais, and Rio de Janeiro) and no study comparing the specimens from different Brazilian states was conducted, we analyzed the genetic distance (16S rDNA, Cyt b, and COI mitochondrial genes) and the chromosomal characteristics for T. vitticeps from Minas Gerais, Rio de Janeiro, and Espirito Santo. All specimens showed the same cytogenetic characteristics. On the other hand, the different mitochondrial genes demonstrated high intraspecific variation between the genetic distances of T. vitticeps from different states ranging from 2.3% to 7.2%. Based on this, our results suggest that possibly what is characterized as T. vitticeps is a complex of cryptic species (or subspecies).